Comparison of Antibacterial Efficacy between 96% Ethanolic Extracts from Abrus precatorius L. and Piper betle L. Leaves against Escherichia coli (Majalah Kedokteran Bandung, 2020)
Escherichia coli (E.coli) is a frequently found infectious pathogen commonly transmitted through water. In Indonesia, the level of this pathogen exceeds the accepted standard. Several studies have shown the presence of antibiotic-resistant E.coli, making studies on alternative treatments for E.coli necessary. Abrus precatorius L. and Piper betle L. leaves are among herbs that have herbal antibacterial properties. This study observed and compared the antibacterial effects of Abrus precatorius L. and Piper betle L. leaves against E.coli. This was an in vitro experimental study performed at the Laboratory of the Department of Microbiology, Faculty of Medicine and Health Science, Atma Jaya Catholic University, from August to November 2019. Abrus precatorius L. and Piper betle L. leaves were extracted by maceration in 96% Ethanol, and further processed into concentrations of 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, and 100%. Disc-diffusion on Mueller-Hinton Agar was used to identify the inhibition zones of the extracts against E.coli ATCC 25922. Ciprofloxacin disc and 96% ethanol impregnated-discs were used as positive and negative controls, respectively. Independent t-test results showed a significant difference between Abrus precatorius L. and Piper betle L. leaves effects against E.coli with p=0.044 and p=0.045 (p
Keywords: Abrus precatorius L.; disc diffusion; Escherichia coli; Piper betle L.